Impact of Myocardial Energy Expenditure and Diastolic Dysfunction on One Year Outcome Patients With HFpEF - Wang, Yu; Cao, Yalan; Xiang, Shuting; Liang, Shunji; Yang, Xiumei; Zhu, Ning; Fang, Weiyi; Yu, Qin (Frontiers in Physiology, 2022)
Abstract Objective: To explore the correlation between characteristics of myocardial energy expenditure (MEE) and the degree of diastolic dysfunction in patients of heart failure with preserved ejection fraction (HFpEF) and its clinical significance. Methods: 125 consecutive patients diagnosed with HFpEF in the Department of Cardiology, Affiliated Zhongshan Hospital of Dalian University from January 2018 to October 2018 were enrolled. According to the degree of diastolic dysfunction, patients were divided into group A (8≤E/e' ≤15) and group B (E/e'> 15), and MEE was calculated, patients finished one-year clinical follow-up. Results: The level of MEE in group A was significantly lower than that in group B (p<0.05). During one-year follow up, MEE over 3145.69 kcal/systole was associated with increased risk of death as compared to patients with MEE less 3145.69 kcal/systole, and in patients with MEE over 101.68 kcal/min than in patients with MEE less than 101.68 kcal/min. Conclusion: There is a significant correlation between MEE and diastolic dysfunction and MEE over 3145.69 kcal/systole as well as MEE over 101.68 kcal/min are linked with increased risk of one-year mortality in HFpEF. Key words：HFpEF；Energy metabolism；diastolic dysfunction；cardiology；MEE